Behind the Wheel: Female Gig Drivers’ Perspectives on Autism Spectrum Disorder in Ride-Sharing Transportation - Nur Alya Batrisyia Mohammad Firdaus; Nur Najwa Dayana Ahmar; Anuar Sani; Sazlina Kamaralzaman (Universiti Kebangsaan Malaysia, 2026)
Tier 3- Indexed by MyCite